1994
DOI: 10.1007/bf00175873
|View full text |Cite
|
Sign up to set email alerts
|

Alternative bases in the RNA world: The prebiotic synthesis of urazole and its ribosides

Abstract: We have prepared a [32P]-labled oligonucleotide probe carrying a free primary amine at its 3'-terminus. This probe is used to initiate polymerization of aziridine (ethyleneimine) in aqueous solution. The nature of the oligomeric products and the kinetics of their formation are then monitored by gel electrophoresis. Our results are generally consistent with those obtained using conventional techniques. We have also investigated the effect of polyanionic templates on the rate of oligomerization of aziridine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 23 publications
1
62
0
2
Order By: Relevance
“…For the comparative reactivity studies of urazoles (Kolb, Dworkin & Miller, 1994), (I) was prepared as reported by Bausch et al (1991) by refluxing equimolar amounts of methylhydrazine and biuret in 1-pentanol for 9 h. The mass of crystals from the cooled mixture was isolated by filtration and recrystallized from ethanol; small, colorless crystals, m.p. 517-518 K (corr; colorless melt) [literature m.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the comparative reactivity studies of urazoles (Kolb, Dworkin & Miller, 1994), (I) was prepared as reported by Bausch et al (1991) by refluxing equimolar amounts of methylhydrazine and biuret in 1-pentanol for 9 h. The mass of crystals from the cooled mixture was isolated by filtration and recrystallized from ethanol; small, colorless crystals, m.p. 517-518 K (corr; colorless melt) [literature m.p.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies of the prebiotic synthesis of urazole (II) and its ribosides (Kolb, Dworkin & Miller, 1994) showed that (II) reacts rapidly with ribose in aqueous solution at room temperature to provide a mixture of a-and /3-furanosides and pyranosides. While 4-methylurazole (III) is very similar to (II) in reactivity and type of products formed, 1-methylurazole (I) failed ....…”
Section: Commentmentioning
confidence: 99%
“…Urea was detected in the Murchison meteorite (Hayatsu et al 1975) and this indicates that some of the urea on early Earth could have been delivered by meteorites. Also very interesting is the observation of larger, urea related compounds together with the hydrazine molecule (N 2 H 4 ), because of the possibility to form urazole (C 2 N 3 O 2 H 3 ) from biuret (H 2 NCONHCONH 2 ) and hydrazine (N 2 H 4 ) under dry conditions as described by Kolb et al (1994). The prebiotic relevance of urazole lies in its role in the ribose phosphate backbone formation as discussed by Kolb et al (1994).…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…Also very interesting is the observation of larger, urea related compounds together with the hydrazine molecule (N 2 H 4 ), because of the possibility to form urazole (C 2 N 3 O 2 H 3 ) from biuret (H 2 NCONHCONH 2 ) and hydrazine (N 2 H 4 ) under dry conditions as described by Kolb et al (1994). The prebiotic relevance of urazole lies in its role in the ribose phosphate backbone formation as discussed by Kolb et al (1994). We cannnot observe urazole or other heterocyclic compounds in our experiment because they do not sublime easily.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…5 Among a large variety of N-containing heterocyclic compounds, those containing Pyrazoles or urazole (1,2,4-triazolidine-3,5-dione) moiety have received considerable attention because of their pharmacological properties and clinical applications. [6][7][8][9] Considering the above reports and in continuation of our research on multi-component reactions [10][11][12][13][14] , Herein we have researched for threecomponent coupling of aldehydes1, malononitrile 2, and 4-phenylurazole 3 in the presence of ZrO 2 nanoparticles to the synthesis of pyrazolo[1,2-a] [1,2,4]triazole-1,3-diones derivatives 4 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%